Development of Educational Game Learning Media "Joko the Explorer" on Regional Diversity Material Grade IV SDN Karangtengah 1 Blitar City - Anggarika, Febyana Setya; Putra, Arda Purnama; Mas’ula, Siti (Journal of Education for Sustainability and Diversity, 2023)
This research is aimed to generate a learning media product of area diversity, called “Joko The Explorer,” in the 4th grade of elementary school, that is interesting and valid to the learning experts, media experts, and the teachers as users. Research with the first trial of 6 students and the second trial of 28 students. ADDIE model, with 5 steps, is used to develop this learning media. The steps are; (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The data-collecting techniques consist of interviews and questionnaires. The questionnaires of learning experts, media experts, and teachers as the users are analyzed by using the Likert scale, whereas the students’ questionnaires are analyzed by using Guttman’s scale. The findings, taken from learning experts, show 93.75%, categorized as strongly valid. The findings from media experts showed 93.75%, categorized as strongly valid. The findings from teachers and the users showed 92.85%, categorized as strongly valid. In terms of attractiveness, the students’ questionnaire responses showed an average of 98,42%, categorized as strongly attractive. The percentage shows that the learning media of educational games, “Joko The Explorer,” is categorized as strongly valid, attractive, and can be used without revision. This research concludes that the learning media product of area diversity, called “Joko The Explorer” in the 4th grade of elementary school, is interesting for the students and strongly valid upon the findings from learning experts, media experts, and teachers as the users. The suggestion for further development is to develop not only in terms of area diversity, but also in broad and deep terms related to the Social Sciences or other sciences.